Perception of emotionally incongruent cues: evidence for overreliance on body vs. face expressions in Parkinson's disease - Abo Foul, Yasmin; Arkadir, David; Demikhovskaya, Anastasia; Noyman, Yehuda; Linetsky, Eduard; Abu Snineh, Muneer; Aviezer, Hillel; Eitan, Renana (Frontiers in Psychology, 2024)
Individuals with Parkinson's disease (PD) may exhibit impaired emotion perception. However, research demonstrating this decline has been based almost entirely on the recognition of isolated emotional cues. In real-life, emotional cues such as expressive faces are typically encountered alongside expressive bodies. The current study investigated emotion perception in individuals with PD (n=37) using emotionally incongruent composite displays of facial and body expressions, as well as isolated face and body expressions, and congruent composite displays as baseline. In addition to a group of healthy controls (HC) (n=50), we also included control individuals with schizophrenia (SZ) (n=30), who display, as in PD, similar motor symptomology and decreased emotion perception abilities. The results show that individuals with PD showed an increased tendency to categorize incongruent face-body combinations in line with the body emotion, whereas HC showed a tendency to classify them in line with the facial emotion. No consistent pattern for prioritizing the face or body was found in individuals with SZ. These results were not explained by the emotional recognition of the isolated cues, cognitive status, depression or motor symptoms of individuals with PD and SZ. As real-life expressions may include inconsistent cues in the body and face, these findings may have implications for the way individuals with PD and SZ interpret the emotions of others.